Subtilisin-like protease 4 regulates cold tolerance through cell wall modification in rice - Jingyan Liu; Fei He; Zhicai Chen; Meng Liu; Yingni Xiao; Ying Wang; YuMeng Cai; Jin Du; Weiwei Jin; Xuejun Liu (Scientific Reports)
Abstract Rice is susceptible to cold temperatures, especially during the seedling stage. Despite extensive research into the cold tolerance mechanisms of rice, the number of cloned genes remains limited. Plant subtilisin-like proteases (SUBs or SBTs) are protein-hydrolyzing enzymes which play important roles in various aspects of plant growth as well as the plant response to biotic and abiotic stress. The rice SUB gene family consists of 62 members, but it is unknown whether they are involved in the response to cold stress. In this study, we observed that a loss-of-function SUB4 mutant exhibited enhanced cold tolerance at the seedling stage. The sub4 mutant seedlings exhibited improved survival rates and related physiological parameters, including relative electrolyte conductivity, chlorophyll content, malondialdehyde content, and antioxidant enzyme activity. Transcriptomic analysis revealed that differentially expressed genes responsive to cold stress in the sub4 mutants were primarily associated with metabolism and signal transduction. Notably, the majority of cold-responsive genes were associated with cell wall functions, including those related to cell wall organization, chitin catabolic processes, and oxidoreductases. Our findings suggest that SUB4 negatively regulates the cold response in rice seedlings, possibly by modifying the properties of the cell wall.